Systemic Inflammatory Response Syndrome Secondary to Nitrofurantoin - Molly R. McGarry PharmD; Meredith W. Wagner MD; Barry M. Wall MD (SAGE Publishing, 2021)
Nitrofurantoin is considered optimal treatment for acute uncomplicated cystitis by the Infectious Diseases Society of America and is being increasingly recommended due to microbial resistance to sulfamethoxazole/trimethoprim and various fluoroquinolone antibiotics. Adverse effects of nitrofurantoin are generally considered mild, with gastrointestinal complaints being the most common. However, there have been isolated case reports describing a more severe systemic inflammatory response syndrome-like reaction, which leads to diagnostic challenges and treatment complications. We report the case of a patient with repeat episodes of systemic inflammatory response syndrome secondary to nitrofurantoin, which was initially attributed to recurrent urinary tract infections.